Occurrence of 17α-ethynylestradiol (EE2) in the environment and effect on exposed biota: a review - Aris, Ahmad Zaharin; Shamsuddin, Aida Soraya; Praveena, Sarva Mangala (Elsevier, 2014)
17α-ethynylestradiol (EE2) is a synthetic hormone, which is a derivative of the natural hormone, estradiol (E2). EE2 is an orally bio-active estrogen, and is one of the most commonly used medications for humans as well as livestock and aquaculture activity. EE2 has become a widespread problem in the environment due to its high resistance to the process of degradation and its tendency to (i) absorb organic matter, (ii) accumulate in sediment and (iii) concentrate in biota. Numerous studies have reported the ability of EE2 to alter sex determination, delay sexual maturity, and decrease the secondary sexual characteristics of exposed organisms even at a low concentration (ng/L) by mimicking its natural analogue, 17β-estradiol (E2). Thus, the aim of this review is to provide an overview of the science regarding EE2, the concentration levels in the environment (water, sediment and biota) and summarize the effects of this compound on exposed biota at various concentrations, stage life, sex, and species. The challenges in respect of EE2 include the extension of the limited database on the EE2 pollution profile in the environment, its fate and transport mechanism, as well as the exposure level of EE2 for better prediction and definition revision of EE2 toxicity end points, notably for the purpose of environmental risk assessment.